2016
DOI: 10.1007/s12028-016-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cerebral Venous and Sinus Thrombosis: Clinical Course, Imaging Correlates, and Prognosis

Abstract: The outcome of severe CVT is almost equally divided between severe impairment or death and survival with no or only mild handicap. Specifically, space-occupying mass effect and associated neurologic deterioration seem to determine a poor outcome. Therefore, early detection and treatment of mass effect should be the focus of critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 20 publications
1
36
1
1
Order By: Relevance
“…The majority of patients who recover completely achieve relative independence, usually expressed as between 0 and 2 on the modified Rankin Scale (mRS), although mild residual symptoms, such as headache, motor deficits, linguistic difficulties, and impaired vision or cognition, often remain . Only 5–10% of patients who survive the acute phase remain moderately or severely dependent (mRS 3 or 4) ; however, this proportion increases up to 34% in those with massive CVST .…”
Section: Prognosismentioning
confidence: 99%
“…The majority of patients who recover completely achieve relative independence, usually expressed as between 0 and 2 on the modified Rankin Scale (mRS), although mild residual symptoms, such as headache, motor deficits, linguistic difficulties, and impaired vision or cognition, often remain . Only 5–10% of patients who survive the acute phase remain moderately or severely dependent (mRS 3 or 4) ; however, this proportion increases up to 34% in those with massive CVST .…”
Section: Prognosismentioning
confidence: 99%
“…Possible explanations are improvements in treatment, a shift in may be achieved in many cases. However, Kowoll et al 6) reported that the mortality rate exceeded 30% in severe-status patients with consciousness disorder (Glasgow coma scale score: ≤9). In patients whose clinical outcome may become poor, endovascular treatment should be positively considered as salvage therapy in addition to anticoagulant risk factors, and, most importantly, the identification of less severe cases by improved diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…1) Anticoagulant therapy reduces the mRS score to 0-2 after 3 months in 94%-95% of patients; 4,5) an improvement in the outcome therapy to promptly and accurately achieve sinus recanalization. As predictors of a severe status or poor outcome, a National Institutes of Health Stroke Scale (NIHSS) score of ≥3 after admission, 6) motor paralysis or sensory disturbance on the initial consultation, 7) brain edema, 8) and an insufficient collateral pathway around the occluded sinus 9) have been reported. In the present case, the condition on arrival was not severe, but brain edema and motor paresis were noted, suggesting that the condition may become severe.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, whether the location of the venous thrombus contributes to cerebrovascular complications is a very controversial matter [2, 3]. The reason for this may be that the clinical manifestations depend on not only the localization of the thrombus but also on the rate of progression and the extent of venous collateralization [4].…”
Section: Introductionmentioning
confidence: 99%